2015
DOI: 10.1063/1.4909552
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding field emission properties of wet-processed titanium dioxide coated carbon nanotube based field emission devices

Abstract: Field emission devices using a wet-processed composite cathode of carbon nanotube films coated with titanium dioxide exhibit outstanding field emission characteristics, including ultralow turn on field of 0.383 V μm−1 and threshold field of 0.657 V μm−1 corresponding with a very high field enhancement factor of 20 000, exceptional current stability, and excellent emission uniformity. The improved field emission properties are attributed to the enhanced edge effect simultaneously with the reduced screening effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Thus, as compared with previously published horizontally aligned monolayer or the vertically aligned MoS 2 NSs or nanoflowers, the as-produced NSs present a clear advantage in terms of low turn-on field and high current density. It has been demonstrated that film morphology of the cathode greatly influences the field-emission performance and the electrons are easier to be extracted from a film with more exposed edges [ 32 ]. Hence, we believe that the tip-like geometry ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, as compared with previously published horizontally aligned monolayer or the vertically aligned MoS 2 NSs or nanoflowers, the as-produced NSs present a clear advantage in terms of low turn-on field and high current density. It has been demonstrated that film morphology of the cathode greatly influences the field-emission performance and the electrons are easier to be extracted from a film with more exposed edges [ 32 ]. Hence, we believe that the tip-like geometry ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ohmic contact and the two‐stage field enhancement together increase the overall field emission performance. A few more recent studies in this domain are cited here and some significant studies are listed in Table .…”
Section: Enhancement (Sources)mentioning
confidence: 99%
“…Among the numerous electron emitters, a thin film of CNTs is considered to be one of the most promising candidates. Though many efforts have been made on the CNT cathode films, the FE performance is not yet satisfactory. Even now, most of the reported data for turn-on electric field ( E to ) and threshold electric field ( E th ) were higher than 1 V/μm despite a few examples. ,, In addition, the field emission stability needs further improvement due to the weak adhesion between CNTs and substrates and/or the susceptibility of pure CNTs to ion bombardment of residual air molecules in the strong electric field . Therefore, it is quite necessary to further improve the field emission performance of CNT films.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, several attempts have been made to enhance the FE properties of CNT cathodes by formation of vertically aligned CNT arrays, , optimization of CNT density, , and modification with various metal nanoparticles, metal oxide thin films, ,, and other nanomaterials with a low work function. ,, Apart from these approaches, crack formation might be another effective way to improve the FE performance as it may simultaneously generate field emission tips and reduce the field screening effect. In fact, it has been employed in several other fields of electronic devices such as cracked electrodes and thin film transistors. , …”
Section: Introductionmentioning
confidence: 99%